2003
DOI: 10.1016/s1074-7613(03)00294-2
|View full text |Cite
|
Sign up to set email alerts
|

GATA-3 Promotes Maturation, IFN-γ Production, and Liver-Specific Homing of NK Cells

Abstract: The GATA-3 transcription factor has a determinant role in T cell specification and is an essential mediator of T helper 2-type polarized immune responses. While both committed NK precursors and mature NK cells express GATA-3, a role of this transcription factor in murine NK cell differentiation is not known. We found that NK cells, in contrast to T cells, can be generated in the absence of GATA-3. However, while GATA-3 antagonizes IFN-gamma production in differentiating T cells, GATA-3-deficient NK cells parad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

12
208
1
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 226 publications
(223 citation statements)
references
References 60 publications
12
208
1
2
Order By: Relevance
“…This hypothesis is supported by the findings that only CD11b low CD43 À NK cells are present in mice deficient for several different transcription factors, such as GATA-3, IRF2 or T-bet, and in mice bearing constitutively active NFkB. In all these models, the CD11b low CD43 À NK cells exhibit normal cytotoxic capacities [38][39][40][41].…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…This hypothesis is supported by the findings that only CD11b low CD43 À NK cells are present in mice deficient for several different transcription factors, such as GATA-3, IRF2 or T-bet, and in mice bearing constitutively active NFkB. In all these models, the CD11b low CD43 À NK cells exhibit normal cytotoxic capacities [38][39][40][41].…”
Section: Discussionmentioning
confidence: 73%
“…Hence, we evidenced opposite effects of CD70 triggering on the major NK cell effector functions. Different outcomes of those NK cell effector functions upon the same triggering have been described before, for example in the GATA-3 deficient mouse model [38]. On the other hand, as several hours are required for ifn-g transcription and translation, the NK cells were incubated for 6 h in the IFN-g assay, during which the higher apoptosis in the mNK cell population of CD70-Tg mice can have an important impact.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Both PLCg2 and PI3K are known to regulate a number of transcription factors. However, their role in regulating transcription factors such as T-bet, 52 GATA-3, 53 IFNregulatory factor-1, 54 IRF-2, 55 ID2, 56 Ets-1, 57 MEF 58 and PU-1 59 that are involved in NK cell development and maturation has yet to be elucidated. Indeed, earlier studies from Di Santo laboratory have shown that lack of GATA-3 reduces the levels of Ly49A, Ly49C/I and Ly49D NK subsets, whereas Ly49G2 and NKG2A/CD94 were unaffected.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, earlier studies from Di Santo laboratory have shown that lack of GATA-3 reduces the levels of Ly49A, Ly49C/I and Ly49D NK subsets, whereas Ly49G2 and NKG2A/CD94 were unaffected. 53 Thus, a lack of transcription factors such as GATA-3 could partially explain the reduction in Ly49 subsets in p85a À/À mice.…”
Section: Discussionmentioning
confidence: 99%